All Inclusive?! Empirical Insights into Individual Experiences of Students with Disabilities and Mental Disorders at German Universities and Implications for Inclusive Higher Education - Janieta Bartz (MDPI AG, 2020)
In the context of the ratification of the UN Convention on the Rights of Persons with Disabilities (CRPD), the German Rectors' Conference has expressed the goal of empowering inclusive education at German universities. The German study "beeinträchtigt studieren" from 2018 indicates that the situation of disabled university students needs to be improved (1). The present case study uses a mixed-methods approach to re-examine the situation of disabled students against the background of individual narratives. One important focus is on accessibility in teaching (2). The study shows that students with disabilities have to deal with many special barriers, among them learning environments, learning materials, and attitudes of teachers-a situation that is further exacerbated by the COVID-19 pandemic (3). Given the results, the question arises as to what measures are useful in ensuring that students do not suffer from stigmatizing or discriminatory experiences during their studies (4). There is a need for further training and development of inclusive teaching methods, such as the Universal Design for Learning (5).